The Clinical Characteristics of Acute Otitis Media at Several Hospitals in Hanoi from 2019 to 2020 - Nhu Dua, Nguyen; Thi Hong Hoa, Doan; Tuan Son, Nguyen; Le Hoa, Nguyen (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2022)
Acute otitis media (AOM) is an infection and accumulation of fluid in the middle ear. The disease usually begins suddenly in a short duration and manifests with the symptoms of ear pain, tinnitus, ear discharge, or hearing loss. Clinical characteristics of acute otitis media in children at several hospitals in Hanoi were described from 2019 to 2020. A cross-sectional descriptive study included 40 patients under 16 years old, diagnosed with AOM, and treated at the Department of Otolaryngology at several hospitals in Hanoi from September 2019 to April 2020. The results indicated that the clinical characteristics of AOM included mild fever (37.5%), moderate fever (20%), high fever (22.5%), unilateral otalgia (57.5%), bilateral otalgia (7.5%), no ear discharge (77.5%), and ear discharge (22.5%). In addition, symptoms accompanied by cough, excessive crying, and digestive disorders accounted for 82.5%, 65%, and 30%, respectively. The main symptoms of AOM are fever and otalgia, accompanied by some co-symptoms such as cough, excessive crying, and digestive disorders.